Advances in imaging of cardiopulmonary involvement in sarcoidosis. Issue 5 (September 2015) - Kouranos, Vasilis; Hansell, David M.; Sharma, Rakesh; Wells, Athol U.
Abstract : Purpose of review: To highlight recent advances of imaging modalities with focus on interstitial lung disease, pulmonary vascular disease and cardiac involvement of sarcoidosis. The contribution of key imaging features to the assessment of disease activity and their impact in the prognostic evaluation and management of sarcoidosis are also described. Recent findings: Imaging plays a central role in the management of patients with sarcoidosis, particularly in the diagnosis and monitoring of disease activity. The correlation of the severity and extent of organ involvement with inflammatory activity helps guide the clinician in determining the optimal treatment strategy for the patient and may also provide prognostic information. The emergence of cardiac MRI and fluoro-deoxyglucose positron emission tomography has enabled an improved understanding of the pathophysiology of sarcoidosis, particularly in relation to cardiac involvement and pulmonary vascular manifestations. Summary: In many patients with pulmonary sarcoidosis, a confident diagnosis can be made based on clinical and imaging features, without the need for histological sampling. In cardiac sarcoidosis, advanced imaging modalities have an increasing role in the identification of active disease, risk stratification and optimal management. Abstract : Supplemental Digital Content is available in the text